Curcumin Regulated the Homeostasis of Memory T Cell and Ameliorated Dextran Sulfate Sodium-Induced Experimental Colitis - Zhong, You-Bao; Kang, Zeng-Ping; Zhou, Bu-Gao; Wang, Hai-Yan; Long, Jian; Zhou, Wen; Zhao, Hai-Mei; Liu, Duan-Yong (Frontiers in Pharmacology, 2021)
Immune memory is protective against re-invasion by pathogens in the homeostatic state, while immune memory disorders can cause autoimmune disease, including inflammatory bowel disease. Curcumin is a natural compound shown to be effective against human inflammatory bowel disease and experimental colitis, but the underlying mechanism is unclear. Here, experimental colitis was induced by dextran sulfate sodium (DSS) in this study. Significant changes in the percentages of naïve, central memory T (TCM), and effector memory (TEM) cells and their CD4+ and CD8+ subsets were found in the peripheral blood of mice with colitis using flow cytometry. After 7 days of continuous curcumin administration, the DSS-induced experimental colitis induced was effectively relieved, with significant decreases in the ratio of day weight to initial body weight, colonic weight, pathological injury score, and levels of pro-inflammatory cytokines IL-7, IL-15, and IL-21, colonic mucosal ulceration; and amount of inflammatory infiltrate. Importantly, curcumin significantly restored the percentages of naïve, TCM, and TEM cells and their CD4+ and CD8+ subpopulations. In addition, curcumin significantly inhibited the activation of the JAK1/STAT5 signaling pathway, down-regulation of JAK1, STAT5, and p-STAT5 proteins, and up-regulation of PIAS proteins. These results suggested that curcumin effectively regulated the differentiation of naïve, TCM, and TEM cells in the peripheral blood to alleviate DSS-induced experimental colitis, which might be related to the inhibition of JAK1/STAT5 signaling activity.